PECULIARITIES OF ANTI-CRISIS MANAGEMENT OF ENTERPRISES IN THE CONTEXT OF ECONOMIC INSTABILITY - Malovanyi, H.; Korzun, N. (Municipal economy of cities. Series: «Economy science», 2024)
The article focuses on identifying the peculiarities of anti-crisis management of construction industry enterprises as leading flagships of the country’s post-war reconstruction and its development in general. Considering the specifics of the analysed enterprise, namely, the peculiarities of its activity, the authors studied the financial indicators of its activity. A distinctive feature of the current period of development of the global and Ukrainian macroeconomy is the instability of the economic environment, and the crisis in the Western financial markets has intensified the development of the crisis in the Ukrainian economy. Under these conditions, many construction companies have found themselves in a crisis due to a decline in the effective demand of the population, customers, and investors. It necessitates adopting evidence-based policy decisions and further targeted actions to restore the lost potential and strengthen the basis for further sustainable development in the global market environment. However, necessary organisational and economic measures that form an enterprise crisis management system, allowing it to maintain a more stable financial position in a crisis, still need to be studied, which is the subject of further research. The set of tools for crisis management of a construction enterprise should include modern information technologies, crisis marketing technologies, analysis methods, and forecasting of the external environment. In crisis management, measures aimed at prompt prevention, response, and overcoming a crisis in modern economic conditions are carried out exclusively using modern information technologies. Based on the above, we can conclude that the main feature of crisis management of a construction company in a crisis is the increased complexity of the management process. It is necessary to make appropriate decisions simultaneously in all areas of the enterprise’s activity: financial stability, sales promotion, and work with clients, suppliers, and financial organisations. It is proved that the crisis is an indicator of the effectiveness of the enterprise and management decisions, which reveals weaknesses.